Plasma interleukin 6 levels are associated with cardiac function after ST-elevation myocardial infarction - Groot, Hilde E. (Clin Res Cardiol, 2018)
BACKGROUND AND AIMS: Myocardial infarction triggers an inflammatory response involved in cardiac repair. We studied the association of the interleukin 6 (IL-6) cascade with infarct size and cardiac function after ST-elevation myocardial infarction (STEMI). METHODS: In 369 STEMI patients IL-6, soluble IL-6 receptor (sIL-6R), and soluble glycoprotein (sgp) 130 were measured at baseline (hospital admission), 24 h, 2 weeks, 7 weeks, 4 months, and 1 year post-PCI and sIL-6R/IL-6 ratio was calculated. At 4 months, infarct size and left ventricular ejection fraction (LVEF) were assessed by magnetic resonance imaging. Diastolic function (E/e′) was determined by echocardiography. RESULTS: Hospital admission levels for IL-6, sIL-6R, sgp 130 were 3.7 pg/ml (IQR 2.1–6.7 pg/ml), 51.6 ng/ml (IQR 37.3–69.0 ng/ml), and 332 ng/ml (IQR 280–399 ng/ml), respectively. 24 h after admission, IL-6 had increased threefold compared to baseline (p < 0.001) and returned below baseline (p < 0.001) 2 weeks after STEMI. sIL-6R and sgp130 levels at 24 h remained similar to baseline but were increased at 2 weeks (p < 0.001; p < 0.001, respectively). IL-6 and sIL-6R/IL-6 ratio at 24 h were independently associated with infarct size [β 5.4 (95% CI 3.3–7.5); p < 0.001, β − 4.0 (95% CI − 6.1 to − 1.9); p < 0.001, respectively]. Higher levels of IL-6 at 24 h were associated with lower LVEF [β − 4.2 (95% CI -6.7 to − 1.8); p = 0.001]. CONCLUSIONS: Higher IL-6 and lower sIL-6R/IL-6 ratio early after presentation with STEMI are indicative for larger infarct size and decreased cardiac function at 4 months. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00392-018-1387-z) contains supplementary material, which is available to authorized users.